A model of culturally‐informed integrated diabetes education and eye screening in indigenous primary care services and specialist diabetes clinics: Study protocol. (10th January 2021) - Atkinson‐Briggs, Sharon; Jenkins, Alicia; Keech, Anthony; Ryan, Christopher; Brazionis, Laima; ,
Abstract: Aims: To improve diabetes management in Indigenous Australians using an integrated nurse‐led model of diabetes education and eye screening in indigenous primary care and specialist diabetes clinics. Design: A pre–post study. Methods: This study will be implemented in indigenous primary care and specialist diabetes clinics in Victoria, Australia. Participants recruited to the study will be existing adult patient with diagnosed diabetes attending study sites. A nurse‐credentialled diabetes educator and certified retinal imager will deliver three study components: (a) retinal photography as a diabetic retinopathy screening and patient engagement tool; (b) lifestyle and behaviour surveys, administered at baseline and at the final visit, in 12 months. Findings from the surveys and participants' retinal images will be used to guide; and (c) personalized diabetes education. The primary outcomes are participant adherence to diabetic eye screening recommendations and health service diabetic retinopathy screening coverage. Secondary outcomes are baseline DR prevalence and changes in clinical and lifestyle risk factor levels, diabetes knowledge and satisfaction with diabetes care. Discussion: Compared with non‐indigenous Australians, Indigenous Australians have a high prevalence of diabetic retinopathy and blindness, low adherence to eye screening recommendations and suboptimal health literacy. Nurse‐credentialled diabetes educators can be trained to incorporate retinal imaging and eye screening into their clinical practice to give image‐based diabetes education to facilitate diabetic retinopathy management. Impact: Credentialled nurse diabetes educators who integrate eye screening and diabetes education can facilitate timelier diabetic retinopathy screening, referral pathways and treatment of sight‐threatening retinopathy. We believe that this model of integrated diabetes education and eye screening will also improve adherence to eye screening recommendations, population screening coverage, health literacy, risk factor levels and diabetes self‐care. Clinical Trial Registration : ANZCTRN1261800120435. 摘要: 目的: 通过在当地初级护理服务和糖尿病专科诊所使用糖尿病教育与眼病筛查的综合护士主导模式, 促进澳大利亚原住民的糖尿病管理。 设计: 一项前后研究。 方法: 此项研究将在澳大利亚维多利亚州的当地初级护理和糖尿病专科诊所实施。此项研究将招募现有成年糖尿病患者的参与者。一名具备护理资质的糖尿病教育者和经认证的视网膜成像仪将提供三个研究组成部分: (a)作为糖尿病视网膜病变筛查和患者参与工具的视网膜成像仪; (b) 生活方式和行为调查, 在12个月的基线检查和最后就诊时进行。调查结果和参与者的视网膜图像将用于指导; (c) 个性化糖尿病教育。主要结果是参与者遵守糖尿病眼筛查建议和健康服务糖尿病视网膜病变筛查覆盖率。次要结果是基线DR患病率、临床和生活方式危险因素水平的变化、糖尿病知识和对糖尿病护理的满意度。 讨论: 与非澳大利亚原住民相比, 澳大利亚原住民患有糖尿病视网膜病变和失明几率较高, 对眼病筛查建议的依从性较低, 且健康素养较差。具备护理资质的糖尿病教育者可接受培训, 将视网膜成像和眼病筛查纳入其临床实践, 以提供基于图像的糖尿病教育, 促进糖尿病视网膜病变的管理。 影响: 有资质的糖尿病护理教育者结合了眼病筛查和糖尿病教育, 因此可促进及时的糖尿病视网膜病变筛查、转诊途径和威胁视力的视网膜病变的治疗。我们相信, 这种糖尿病教育和眼病筛查的综合模式还将提高对眼病筛查建议、人群筛查覆盖率、健康素养、风险因素水平和糖尿病自我护理的依从性。 临床试验注册: ANZCTRN1261800120435.